Determinants of Investment in The Consumer Goods Sector with Stock Prices as Intervening Variables - Sanusi, Adelia Nur Arafah Aprilia; Pahlevi, Cepi; Nohong, Mursalim (Hasanuddin Economics and Business Review, 2023)
The objective of this study is to assess the impact of Current Ratio, Debt to Equity Ratio, and Total Asset Turnover on Return on Investment (RoI), while Stock Prices as intervening factors. The analysis focuses specifically on Manufacturing Companies within the Consumer Goods sector that are listed on the IDX. This research is quantitative research with a descriptive analysis approach. The data collected were analyzed with formulas from each financial ratio and then processed using multiple regression analysis and sobel tests. The results of this study indicate that CR is not significant on Stock Price, while DER is related to Stock Price with a negative effect. Finally, TATO has a significant impact on Stock Price, with a positive sign on the relationship. Stock Price, CR and TATO have positive and significant effect on ROI, while DER have negative and significant effect on ROI, CR through stock price has no effect on ROI, while DER and TATO through share price affects ROI in Manufacturing Companies in the Goods Sector Consumption listed on the IDX.